2015
DOI: 10.1136/bmjopen-2015-009826
|View full text |Cite
|
Sign up to set email alerts
|

Understanding burn injuries in Aboriginal and Torres Strait Islander children: protocol for a prospective cohort study

Abstract: IntroductionAlthough Aboriginal and Torres Strait Islander children in Australia have higher risk of burns compared with non-Aboriginal children, their access to burn care, particularly postdischarge care, is poorly understood, including the impact of care on functional outcomes. The objective of this study is to describe the burden of burns, access to care and functional outcomes in Aboriginal and Torres Strait Islander children in Australia, and develop appropriate models of care.Methods and analysisAll Abor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 19 publications
0
30
0
Order By: Relevance
“…CBPR has been used to facilitate initiatives related to photovoice (Castleden et al, 2008), story-telling (Christensen, 2012), multi-method research including focus groups (Garakani, 2014), semi-structured interviews (Cameron et al, 2014;Ivers et al, 2015), web-based surveys (Fox et al, 2011), yarning (Russell-Mundine, 2007, and other mixed-method approaches (Le & Gobert, 2015). The adaptability of CBPR values has been praised as a way to ensure research is completed in accordance with local norms and customs of communities through their chosen research method (Christensen, 2012).…”
Section: Community-based Participatory Research (Cbpr)mentioning
confidence: 99%
“…CBPR has been used to facilitate initiatives related to photovoice (Castleden et al, 2008), story-telling (Christensen, 2012), multi-method research including focus groups (Garakani, 2014), semi-structured interviews (Cameron et al, 2014;Ivers et al, 2015), web-based surveys (Fox et al, 2011), yarning (Russell-Mundine, 2007, and other mixed-method approaches (Le & Gobert, 2015). The adaptability of CBPR values has been praised as a way to ensure research is completed in accordance with local norms and customs of communities through their chosen research method (Christensen, 2012).…”
Section: Community-based Participatory Research (Cbpr)mentioning
confidence: 99%
“…Indigenous Australian children are disproportionally affected: they are more than twice as likely to be hospitalised for a burn injury as non‐Indigenous children, and mortality is five times as high 2 . ‐ 4 Despite this high burden, little is known about the characteristics of burn injuries to Indigenous children or whether they differ from those to non‐Indigenous children 5 …”
mentioning
confidence: 99%
“…The authors also found that the proportion of burn injuries affecting more than 20% of total body surface area (TBSA) was greater for Indigenous than for non‐Indigenous children, as was that of burns to the feet or ankles; that the incidence of being treated in a tertiary burns facility was lower and their median overall hospital stay longer for Indigenous children; and that they were less likely to undergo surgery, but more frequently received treatment from allied health professionals. This important epidemiological study not only supports the hypothesis that burn injuries constitute a significant health burden in Indigenous children, it is also the prelude to a much larger prospective study 5 . Paediatric burns services throughout Australia are currently collaborating in a study funded by the National Health and Medical Research Council to examine the journey of the Indigenous child with a burn injury through the health system, including pre‐hospital care and outpatient follow‐up 5 …”
mentioning
confidence: 59%
“…This important epidemiological study not only supports the hypothesis that burn injuries constitute a significant health burden in Indigenous children, it is also the prelude to a much larger prospective study 5 . Paediatric burns services throughout Australia are currently collaborating in a study funded by the National Health and Medical Research Council to examine the journey of the Indigenous child with a burn injury through the health system, including pre‐hospital care and outpatient follow‐up 5 …”
mentioning
confidence: 59%